Analisis Estimasi Biaya Langsung Medis Penderita Rawat Jalan Diabetes Mellitus Tipe 2 di RSUD Dr. Abdul Aziz Singkawang Tahun 2013 - Mursalin, Mursalin; Soewondo, Prastuti (UI Scholars Hub, 2016)
Diabetes mellitus is an epidemic disease that seriously threatens global health. In addition to the high levels of morbidity and mortality, it also causes many countries around the world to spend a significant amount of money on healthcare. This study aims to calculate the direct medical costs and influencing factors of type 2 diabetes mellitus outpatient care. The study was conducted from January to February 2015 at RSUD dr. Abdul Aziz Singkawang in West Kalimantan. The study design used quantitative analysis with secondary data retrospectively collected from 2013, with a sample size of 200. The results of the multivariate analysis showed significant differences in the direct medical costs of type 2 diabetes mellitus outpatient care based on the type of care, disease duration, and complications. Health promotion and prevention interventions for type 2 diabetes mellitus should be increased to achieve effective and efficient care costs and to improve patients' quality of life.